2014
DOI: 10.1371/journal.pone.0116026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms in VDR and DBP Genes with HBV-Related Hepatocellular Carcinoma Risk in a Chinese Population

Abstract: BackgroundPolymorphisms of genes encoding components of the vitamin D pathway including vitamin D receptor (VDR) and vitamin D binding protein (DBP) have been widely investigated because of the complex role played by vitamin D in cancer tumorogenesis. In this study, we investigated the association between VDR and DBP gene polymorphisms and HBV-related HCC risk in a Chinese population.MethodsStudy subjects were divided into three groups: 184 HBV patients with HCC, 296 HBV patients without HCC, and 180 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 38 publications
3
43
1
Order By: Relevance
“…Moreover, it had been reported that the antiproliferative effects of vitamin D against HCC cells correlate with intracellular VDR level [44,51]. Also, it had been reported that polymorphism at FokI locus was associated with increased HCC susceptibility in Egyptian patients infected with chronic hepatitis B and had a significant role in the determination of its clinicopathological characteristics [48,26]. VDR gene SNPs (ApaI CC genotypes, CCA[bAt]-haplotype and Taq AA genotype) were also reported to be significantly associated with high hepatitis C virus load but not with antiviral (peginterferon plus ribavirin) response in chronic HCV Asian patients [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it had been reported that the antiproliferative effects of vitamin D against HCC cells correlate with intracellular VDR level [44,51]. Also, it had been reported that polymorphism at FokI locus was associated with increased HCC susceptibility in Egyptian patients infected with chronic hepatitis B and had a significant role in the determination of its clinicopathological characteristics [48,26]. VDR gene SNPs (ApaI CC genotypes, CCA[bAt]-haplotype and Taq AA genotype) were also reported to be significantly associated with high hepatitis C virus load but not with antiviral (peginterferon plus ribavirin) response in chronic HCV Asian patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…VDR gene polymorphisms have been described in several chronic liver diseases such as liver cirrhosis [21], autoimmune hepatitis [22], primary sclerosing cholangitis [23] and primary biliary cirrhosis [24]. Moreover, it has been reported that there is a significant association between polymorphisms of VDR gene and the occurrence of HCC in alcoholic liver cirrhosis in Caucasian subjects [25], in HBV-infected patients [26] and even in patients with chronic HCV [27]. However, the data in the literature describing the possible association between VDR gene polymorphisms and hepatocellular carcinoma (HCC) development are scarce and inconclusive especially in patients infected with HCV.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D binding protein polymorphisms were associated with hepatocellular carcinoma in hepatitis B virus (HBV) patients but to date, there are no studies to assess its role in predicting response to HBV therapy, therefore further research is encouraged in that area [44]. Similarly, vitamin D binding protein polymorpshisms have been associated with insulin resistance in chronic hepatitis C (CHC) patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…Nine single nucleotide polymorphisms (SNPs) of three critical genes in vitamin D metabolic pathway were genotyped, including VDR (rs7975232/ ApaI , rs1544410/ BsmI , rs757343/ Tru9I , rs2228570/ FokI , rs731236/ TaqI ), VDBP (rs4588, rs7041), 1α‐hydroxylase (cytochrome P450, family 27, subfamily b, polypeptide 1, CYP27B1 ) (rs10877012, rs3782130) …”
Section: Methodsmentioning
confidence: 99%